Facile Route to Generate Fuel Oil via Catalytic Pyrolysis of Waste Polypropylene Bags: Towards Waste Management of >20 μm Plastic Bags. (2nd January 2014) - Mishra, Neeraj; Pandey, Sunil; Patil, Bhushan; Thukur, Mukeshchand; Mewada, Ashmi; Sharon, Madhuri; Sharon, Maheshwar
Abstract : A novel strategy of waste recycling of polypropylene plastics (PP) bags for generation of commercially viable byproducts using nanoforms of nickel as catalyst is presented in this work. After pyrolysis of waste PP bags (>20  μ m) under continuous argon flow, 90% conversion efficiency to high petroleum oil was observed at 550°C. To assess the physicochemical attributes of formed oil, flash point, pour point, viscosity, specific gravity, heating value, and density were also measured and found to be very close to ideal values of commercial fuel oil. Moreover, GC-MS was used to resolve the range of trace mass hydrocarbon present in the liquefied hydrocarbon. Our robust recycling system can be exploited as economical technique to solve the nuisance of waste plastic hazardous to ecosystem.